2017
DOI: 10.1038/nsmb.3433
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine endopeptidase cleaves α-synuclein and mediates pathologic activities in Parkinson's disease

Abstract: Aggregated forms of α-synuclein play a crucial role in the pathogenesis of synucleinopathies such as Parkinson’s disease (PD). However, the molecular mechanisms underlying the pathogenic effects of α-synuclein are not completely understood. Here we show that asparagine endopeptidase (AEP) cleaves human α-synuclein, triggers its aggregation and escalates its neurotoxicity, thus leading to dopaminergic neuronal loss and motor impairments in a mouse model. AEP is activated and cleaves human α-synuclein at N103 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
167
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 46 publications
8
167
0
Order By: Relevance
“…It is worth noting that both MAO‐B and α‐Syn protein levels were higher in PD patients than healthy controls. We have recently reported that AEP, an age‐dependent cysteine protease, is highly activated in human PD brains and cleaves α‐Syn at N103, promoting its aggregation and neurotoxicity (Zhang et al , ). Accordingly, α‐Syn N103 was much more abundant in PD brains than controls (Fig E).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth noting that both MAO‐B and α‐Syn protein levels were higher in PD patients than healthy controls. We have recently reported that AEP, an age‐dependent cysteine protease, is highly activated in human PD brains and cleaves α‐Syn at N103, promoting its aggregation and neurotoxicity (Zhang et al , ). Accordingly, α‐Syn N103 was much more abundant in PD brains than controls (Fig E).…”
Section: Resultsmentioning
confidence: 99%
“…Asparagine endopeptidase is an age‐dependent protease that cleaves α‐Syn in PD brains (Zhang et al , ). Wild‐type SNCA transgenic mice display PD‐like pathology and motor deficits between 12 and 18 months of age (Janezic et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations